2014
DOI: 10.1007/s11055-014-0017-0
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Dependent Actions of the Histone Deacetylase Blocker Sodium Valproate on Olfactory Learning in 129Sv Mice during the Early Postnatal Period

Abstract: The mechanisms supporting the long-term stable effects of early experience consist of modifications to chromatin, including histone acetylation, leading to changes in the structural relationships between DNA and histones [8,13,15,21]. Increases in levels of histone acetylation in brain and in the transcriptional activity of genes after treatment of animals with histone deacetylase blockers lead to improvements in learning [11,18,22]. This same effect is produced by high levels of maternal care in the first wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Preferential response to valproate has been previously reported: valproate administration has a significant effect on male, but not female, performance in some behavioral paradigms ( Burenkova et al, 2013 ). Further, while valproate has been shown to have neuroprotective effects in models of neurodegeneration, these effects are more substantial in males than in females ( Long et al, 2016 ).…”
Section: Discussionmentioning
confidence: 80%
“…Preferential response to valproate has been previously reported: valproate administration has a significant effect on male, but not female, performance in some behavioral paradigms ( Burenkova et al, 2013 ). Further, while valproate has been shown to have neuroprotective effects in models of neurodegeneration, these effects are more substantial in males than in females ( Long et al, 2016 ).…”
Section: Discussionmentioning
confidence: 80%
“…However, with the administration of smaller doses (such as 50 mg/kg), these effects are not observed (Johannessen & Johannessen, 2003). In our experiments, we showed that the blockade of HDACs by sodium valproate administered subcutaneously at a dose of 50 mg/kg on PND3‐6 led to an improvement in olfactory discrimination learning task with imitation of maternal grooming as positive reinforcement impaired by MS procedure in a gender‐dependent manner, that is, in males, but not in females (Burenkova et al., 2014b). At the same time, the use of this scheme of administration of valproate did not lead to a violation of the physical, somatosensory development and social behavior of 129Sv mice in the nesting period (Burenkova et al., 2015).…”
Section: Pharmacological Interventions and Epigenetic Editing As Tool...mentioning
confidence: 90%
“…Taking into account the negative impact of MS during the first postnatal week on subsequent behavior of adult female offspring, our next intention was to study the possibility of prevention of this influence. For this purpose we proposed the use of pharmacological agent modulating these mechanisms, VPA which restored the olfactory discrimination learning of 129Sv neonatal mice impaired by MS in our previous work (Burenkova, Aleksandrova, & Zarayskaya, 2013). In response to a question—whether early life administration of VPA could restore the negative effects caused by early stress—mixed results have been revealed.…”
Section: Discussionmentioning
confidence: 99%